INFLUENCE OF KNOWLEDGE MANAGEMENT ON INNOVATIVE BEHAVIOR AND ITS IMPACT ON MANAGERIAL PERFORMANCE OF MEDIUM-SCALE BATIK INDUSTRY OWNERS IN WEST JAVA, INDONESIA - Hamidah; Ernie Trisnawati Sule; Yunizar; Rina Novianti Ariawaty (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Managerial performance of the batik industry is a condition in which batik business owners can conduct management functions. The competition with batik-patterned textile products and the lack of public understanding of using batik as a form of appreciation for their domestic products are the biggest challenges faced by batik entrepreneurs. This study aims to determine empirically the influence of knowledge management on innovative behavior and its impact on managerial performance of medium-scale batik industry owners in West Java. This study uses mixed-method research. Quantitative methods use a questionnaire as the dominant instrument to obtain the main data, while the qualitative method uses semi-structured interviews, focus group discussion with Delphi techniques, and observations to the batik industry. Variant-based structural equation modeling with partial least square is the analytical tool utilized to test the hypothesis and determine the relationship between variables. The research variables comprised the following: exogenous (knowledge management), endogenous (managerial performance), and intervening (innovative behavior) variables. Research results prove the following. 1) Knowledge management has a positive effect on innovative behavior. 2) Innovative behavior has a positive effect on managerial performance. 3) Knowledge management has a positive effect on managerial performance. 4) Knowledge management through innovative behavior has a positive effect on managerial performance.